MULTICULTURALISM IN ETHNIC IN CHILDREN'S POPULAR FILM IN INDONESIA POST 2010 - Rozi, Romdhi Fatkhur (Seni Media Rekam ISI Surakarta, 2019)
This article discusses about multiculturalism in the popular film industry with the theme of children in Indonesia after 2010. The categorization of this popular film is based on the number of viewers. This study is intended to find many aspects of ethnic multiculturalism contained in child-theme films after 2010. The concept of children's films from Bezalgette and Stapless is used to review the children's theme films. The conclusions of this study are that multiculturalism is present in most children's films in Indonesia through various forms of moral messages, which are delivered from interactions between characters and characterizations, however the films have not succeeded in showing all multi-ethnic diversity in Indonesia yet.